Efforts and Barriers Shifting a City Region Towards Circular Transition – Lessons from a Living Lab from Pécs, Hungary. (13th September 2022) - Varjú, Viktor; Óvári, Ágnes; Mezei, Cecília; Suvák, Andrea; Vér, Csaba
A Circular Economy is usually seen as achieving 'zero waste' and closing the material flow loops. However, multiple governance, economic, legal, socio-spatial, cultural, and behavioural barriers may easily hamper the transition. This study summarises the lessons learned from the waste flow analysis and living lab (LL) of a case study from the H2020 REPAiR project. It shows how the results of a waste flow analysis created for an urban area can help decision-makers to co-create new place-based eco-innovative solutions and hence shift the city towards circularity. At the same time, during the living lab process, it became clear that the decision support method alone is not enough to co-create or co-design new innovations, in addition the regulatory environment and the peculiarities of governance may also present multiple obstacles. The centralised governance in Hungary and the centralisation tendency in waste management and secondary resource use hamper efficient local resource management. The work in the LL showed that a centralised governance structure hinders not only the co-creation of new solutions but also the transfer of good practices from other peri-urban areas. This is important because a society that is generally less innovative and less developed at the beginning of sustainability transition is innovating for the first time via the transfer of eco-innovative solutions. Our paper shows that the governance structure of a given spatial unit (i.e. a city region) may be a significant factor in the successful or unsuccessful adoption of good practices and for the circular transition, as may system adaptability, the level of local technological development, the level of integration of actors, strategies, interests, and policy interventions.